2019
DOI: 10.1021/jacs.8b12634
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Role of Ligand Electronics on Stabilizing Electrocatalytically Relevant Low-Valent Co(I) Intermediates

Abstract: Cobalt complexes have shown great promise as electrocatalysts in applications ranging from hydrogen evolution to C−H functionalization. However, the use of such complexes often requires polydentate, bulky ligands to stabilize the catalytically active Co(I) oxidation state from deleterious disproportionation reactions to enable the desired reactivity. Herein, we describe the use of bidentate electronically asymmetric ligands as an alternative approach to stabilizing transient Co(I) species. Using disproportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 80 publications
(31 reference statements)
2
82
0
1
Order By: Relevance
“…Further investigation of the nickel complex 5 were conducted. CV studies in DMA as a solvent and KBr as a supporting electrolyte showed more complex behavior (see the Supporting Information) . Thus, DFT calculations for the oxidative addition step at Ni 0 were conducted (Figure a; see the Supporting Information computational methods).…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation of the nickel complex 5 were conducted. CV studies in DMA as a solvent and KBr as a supporting electrolyte showed more complex behavior (see the Supporting Information) . Thus, DFT calculations for the oxidative addition step at Ni 0 were conducted (Figure a; see the Supporting Information computational methods).…”
Section: Resultsmentioning
confidence: 99%
“…This could be seen as there are two reduction peaks and they could be plausibly assigned as E = À1.70 V vs. SCE for the reduction of cobalt(II) to cobalt(I) and E = À1.95 V vs. SCE for the reduction of cobalt(I) to cobalt(0) (Figure 3 b). [24] The reduction of cobalt(III) to cobalt(II) was not observed as it has a much higher potential, usually in the positive range. [25] These results indicate that the oxidative addition of the substrate onto the active cobalt catalyst is possibly not involved in the rate-determining step.…”
Section: Methodsmentioning
confidence: 99%
“…Minteer and Sigman utilized cyclic voltammetry (CV) and square wave voltammetry (SWV) to study the thermodynamic and kinetic profile of a series of Co I complexes with bidentate N , N -ligands that are relevant to electrocatalysis ( Figure 12 ). 50 In combination with multivariate linear regression analysis and various other experimental and theoretical techniques, the mechanism of Co I disproportionation—an undesired catalyst decomposition pathway—was studied in great detail. This study also led to the identification of an electronically asymmetric pyrox ligand ( 12 - 1 ) that both promotes desired oxidative addition of Co I to benzyl bromide and suppresses the deleterious disproportionation pathway.…”
Section: Electrochemistrymentioning
confidence: 99%